Structural and parametrical planning of informative systems DPLA for operative natural resource and ecological monitoring of environment - Зосимович, Н В.; Мазур, В. И. (Problems of Informatization and Control, 2007)
On the basis of method of structural and parametrical planning the method of planning of the state of the systems of sides is offered, nashlemnykh control systems and arrangement of the informatively-managing field of surface complex of management the distance-piloted aircrafts for operative natural resource and ecological monitoring of environment